Knowledge About Genetics in Congenital Hearing Loss: A Survey Among Audiologists - Kaur, Navleen; Deshpande, Shweta (Journal of Health and Allied Sciences NU, 2024)
Introduction According to the World Health Organization, there are more than 63 million people in India who have disabling hearing loss. Hearing loss at birth can be caused due to genetic factors. Referral for genetic testing and counseling can be directly influenced by the knowledge among the audiologists. Specific guidelines and recommendations have been provided by experts in the field for competency in genetics among professionals to ensure early and appropriate management in young children with hearing loss. In India, there is limited research done on assessing audiologists' knowledge concerning the importance of genetic testing and counseling. Thus, the present study aimed to explore the knowledge about the role of genetics in congenital hearing loss among audiologists.Method The study was conducted in two phases. Phase I included the development and validation of the questionnaire. Phase II included the administration of the questionnaire to the professionals from the field of audiology and speech-language pathology through Google Forms.Results The study findings revealed that the knowledge level about general genetics was adequate; however, aspects related to genetic testing and syndromic and nonsyndromic congenital hearing loss were moderate. There was a statistically significant difference observed in the scores obtained by professionals who had completed Master of Science in Audiology as compared to those who had completed Bachelors in Audiology and Speech Language Pathology and Masters in Audiology and Speech Language Pathology.Conclusion The study has highlighted the current knowledge of audiologists with respect to domains of genetic testing and syndromic and nonsyndromic congenital hearing loss. There is a need to educate audiologists working in the area of early identification and intervention about the genetic basis of hearing loss.
Keywords: audiologists; genetics; syndromic and nonsyndromic hearing loss